Characterization of phytopathogenic fungi, bacteria, nematodes and viruses in four commercial varieties of heliconia (heliconia sp.) / caracterización de hongos, bacterias, nemátodos y virus fitopatógenos en cuatro variedades comerciales de heliconia (2012)
Analysis of 914 samples of roots, rhizomes, pseudostems, inflorescences and leaves of four commercial varieties of heliconia, cultivated at the municipality of Chinchiná– Caldas (Colombia), allowed to identify five genera of plant pathogenic fungi (Rhizoctonia, Fusarium, Colletotrichum, Helminthosporium and Curvularia), three genera of plant pathogenic bacteria (Ralstonia, Pseudomonas and Erwinia), two species of viruses (Banana streak virus (BSV, Badnavirus,) and Cucumber mosaic virus (CMV, Cucumovirus,)), and seven genera of plant parasitic nematodes (Helicotylenchus, Tylenchus, Meloidogyne, Ditylenchus, Aphelenchoides, Pratylenchus, and Radopholus). Of these, Fusarium sp., affecting pseudostems, Pseudomonas sp., affecting leaves and inflorescences, and the plant parasitic nematodes Ditylenchus sp., Aphelenchoides sp., Pratylenchus sp. and Radopholus sp., are new records in the heliconia production in Colombia. The most limiting diseases corresponded to leaf blight, caused by Helminthosporium sp.; the bacterioses, caused by Pseudomonas sp.; the spotted stems, caused by Fusarium sp.; and soft rot of the pseudostems, caused by Erwinia sp. The pathogenicity tests demonstrated that Colletotrichum sp. and Phoma sp. are not pathogenic in leaves; while Fusarium sp., inoculated in pseudostems, Helminthosporium sp. and Pseudomonas sp., inoculated in leaves, and Colletotrichum sp. and Pseudomonas sp., inoculated in inflorescences, had incidence values of 83.3, 86.6, 93.3, 100.0 and 100.0%, respectively. / El análisis de 914 muestras de raíces, rizomas, pseudotallos, inflorescencias y hojas de cuatro variedades comerciales de heliconia, cultivadas en el municipio de Chinchiná–Caldas (Colombia), permitieron identificar cinco géneros de hongos fitopatógenos (Rhizoctonia, Fusarium, Colletotrichum, Helminthosporium y Curvularia), tres géneros de bacterias fitopatógenas (Ralstonia, Pseudomonas y Erwinia), dos especies de virus (Banana streak virus (BSV, Badnavirus,) y Cucumber mosaic virus (CMV, Cucumovirus,)), y siete géneros de nematodos fitoparásitos (Helicotylenchus, Tylenchus, Meloidogyne, Ditylenchus, Aphelenchoides, Pratylenchus y Radopholus). De ellos, Fusarium sp., afectando pseudotallos, Pseudomonas sp., afectando hojas e inflorescencias, y los nematodos fitoparásitos Ditylenchus sp., Aphelenchoides sp., Pratylenchus sp. y Radopholus sp., son reportes nuevos en la producción de heliconias en Colombia. Las enfermedades más limitantes correspondieron al tizón foliar, causado por Helminthosporium sp.; la bacteriosis, causada por Pseudomonas sp.; el manchado de pseudotallos, causado por Fusarium sp.; la pudrición de calcetas, causada por Erwinia sp.; y el moko, causado por Ralstonia solanacaearum. Las pruebas de patogenicidad demostraron que Colletotrichum sp. y Phoma sp. no son patogénicos en hojas; mientras que Fusarium sp., inoculado en pseudotallos, Helminthosporium sp. y Pseudomonas sp., inoculados en hojas, y Colletotrichum sp. y Pseudomonas sp., inoculados en inflorescencias, presentaron valores de incidencia de 83,3, 86,6, 93,3, 100,0 y 100,0%, respectivamente.